Polymer-based Solid-State Batteries - Brandell, Daniel; Hernández, Guiomar; Mindemark, Jonas (De Gruyter, 2021)
Recent years has seen a tremendous growth in interest for solid state batteries based on polymer electrolytes, with advantages of higher safety, energy density, and ease of processing. The book explains which polymer properties guide the performance of the solid-state device, and how these properties are best determined. It is an excellent guide for students, newcomers and experts in the area of solid polymer electrolytes.
Keywords: Solid state batteries -- Materials.; Storage batteries -- Materials.; Polyelectrolytes.; elektronické knihy; electronic books